FORMULASI STRATEGI HOTEL DANAU DARIZA MENGGUNAKAN ANALISIS SWOT DAN QSPM MATRIX - Tefirmansyah, Salwa Khoirunnisa; Alamsyah, Muhammad Iqbal (eProceedings of Management, 2025)
Hotel Danau Dariza is one of the leading accommodations in Garut Regency, featuring traditional architecture inspired by local cultural heritage. However, the hotel has experienced a decline in occupancy rates due to increasing competition and shifting tourist preferences toward digitalized services. This study aims to formulate an effective business development strategy to enhance the hotel’s competitiveness. The research employs a descriptive qualitative approach using the Quantitative Strategic Planning Matrix (QSPM), which includes the input stage (IFE and EFE matrices), matching stage (SWOT and IE matrices), and decision stage (QSPM). The analysis results indicate that Hotel Danau Dariza falls into the